An evaluation of variables affecting the stability and performance of down-flow anaerobic fixed bed reactors treating piggery wastewater - Sánchez, E (2006)
The influence of the most important variables on the stability and performance of down-flow anaerobic fixed bed reactors treating piggery wastewater after primary sedimentation was evaluated at HRT in the range of 1-6 d and influent substrate concentration in the range of 2 to 12 g TCOD 1-(1). The effect of HRT was more pronounced compared to that of influent strength. An increase in the HRT increased the process stability and process performance at different influent strengths. TCOD, SCOD, BOD5, TSS, organic nitrogen (N) and Orthophosphate (P) removals increased with the HRT, independently of the initial substrate concentration (S-0). The increase in S-0 brought about an increase in the attached biomass concentration (X) at the end of the experiment. Two empirical models based on the individual effect of HRT, X and S-0 were evaluated and found to be adequate to describe the influence of these variables on the process performance. The first model took all the above-mentioned variables into consideration while the second model was simplified and based on the use of HRT as the only independent variable. The results obtained by using both models were found to be similar. This demonstrated that independently of the characteristics of the operation, the behaviour and performance of the reactors were comparable. The methane yield coefficient was found to be 0.3371 methane g(-1) TCOD removed.